Qualitative analysis of teeth and evaluation of amalgam elements penetration into dental matrix using laser induced breakdown spectroscopy - Gazmeh, Meisam; Bahreini, Maryam; Tavassoli, Seyed Hassan; Asnaashari, Mohammad (Journal of Lasers in Medical Sciences, 2015)
In this study, laser induced breakdown spectroscopy (LIBS) is used for qualitative analysis of healthy and carious teeth. The technique of laser ablation is receiving increasing attention for applications in dentistry, specifically for the treatment of teeth such as drilling of micro-holes and plaque removal. In the process of ablation a luminous micro-plasma is normally generated which may be exploited for on-line elemental analysis via laser induced breakdown spectroscopy technique. We propose laser induced breakdown spectroscopy as a rapid, in situ and easy method for monitoring drilling process. The results of elemental analysis show the presence of some trace elements in teeth including P, Ca, Mg, Zn, K, Sr, C, Na, H, O and the permeability of some amalgam (teeth filling materials) elements including Hg, Ag, Cu and Sn into dental matrix. This study address the ability of LIBS in elemental analysis of teeth and its feasibility in acute identification of healthy and carious teeth during drilling process for future clinical applications.